2020
DOI: 10.32628/cseit2063197
|View full text |Cite
|
Sign up to set email alerts
|

A Survey On Air Quality Prediction Using Traditional Statistics Method

Abstract: Air pollution is the release of pollutants into the atmospheric air which are harmful to human health and the planet as a whole. Car emissions, dust, pollen, chemicals from factories and mold spores may be suspended as a particle. In this survey, the analyzes are made revolving on air quality prediction using the traditional statistics method. The prediction using air pollutants are PM2.5, PM10, NO2, NOx, NO, SO2, CO, O3 and meteorological parameters such as Absolute Temparathure(AT) and Relative Humidity(RH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For shorter-term forecasting, ARIMA coupled with the Holt exponential smoothing model was utilized to forecast daily AQI values [22]. More recent work proposed a survey comparing classical statistical models for AQI forecasting and concluded that ARIMA models were superior in mapping trends and producing predictions with the lowest root mean square error (RMSE) compared to other statistical models [23]. Nevertheless, the majority of statistical-based models consider only previously recorded data to forecast the following ones without accounting for the effect of atmospheric variables and conditions.…”
Section: Related Workmentioning
confidence: 99%
“…For shorter-term forecasting, ARIMA coupled with the Holt exponential smoothing model was utilized to forecast daily AQI values [22]. More recent work proposed a survey comparing classical statistical models for AQI forecasting and concluded that ARIMA models were superior in mapping trends and producing predictions with the lowest root mean square error (RMSE) compared to other statistical models [23]. Nevertheless, the majority of statistical-based models consider only previously recorded data to forecast the following ones without accounting for the effect of atmospheric variables and conditions.…”
Section: Related Workmentioning
confidence: 99%